A Parallel Distributed Model of the Psychological Disciplines and Professions - Lachenicht, Lance (PINS-Psychology in Society, 2026)
Most psychologists in South Africa would admit that a non-reductive model of the relations between individual psychologists and the psychological professions (the individual interaction versus structure relationship - a central problem of sociology [see Giddens, 1984]) combined with a non-reductive model of the relations between the psychological sub-disciplines and professions would be something well worth having at a time of transformation and reconstruction. A search of the sociological and social psychological literatures will yield few promising candidates for such a model. One exception is the newly developed model of scientific disciplines as (to use Minsky’s (1986) phrase literally) societies of minds, based upon the model of parallel distributed processing. (Minsky’s phrase societies of minds is being used literally here because Minsky is actually referring to "agents• internal to the individual that carry out cognitive tasks rather than to individuals who exist in a real society.) Gigerenzer, a cognitive psychologist and an historian of psychology, has suggested that psychologists regularly make use of the "tools to theories heuristic" in which scientists tend to use their tools, which they have come to understand well, as metaphors for the subject they are trying to understand - in the case of psychologists, the mind (Gigerenzer & Murray, 1987).